Pathways to integrate Indigenous and local knowledge in ocean governance processes: Lessons from the Algoa Bay Project, South Africa - Rivers, Nina; Strand, Mia; Fernandes, Meredith; Metuge, Denning; Lemahieu, Anne; Nonyane, Chilo Loyolah; Benkenstein, Alex; Snow, Bernadette (Frontiers in Marine Science, 2023)
The Introduction of this paper argues that current coastal and ocean management approaches like marine spatial planning (MSP) often do not adequately acknowledge and integrate Indigenous and Local Knowledge (ILK). This is problematic because how humans value and perceive coastal and marine resources is integrally linked to how they use and manage these resources, especially in adapting to social-ecological change. Coastal and marine resources are situated within complex social-ecological systems that are culturally, economically, historically and politically embedded. Therefore, management approaches have to integrate transdisciplinary and contextual perspectives in order to be relevant, sustainable and adaptive. Following extensive research in Algoa Bay, South Africa this article highlights several pathways to bridge the gap between existing ILK and current coastal and ocean management approaches. The Methods section discusses how the authors worked in tandem with a bottom-up (engaging with Indigenous and local coastal and marine resource users) and top-down (engaging with coastal governance authorities and practitioners) approach. In order to answer the primary research question “How can ILK be integrated into area-based ocean management like MSP”? the authors employed arts-based participatory methods as well as in-depth interviews and workshops with coastal governance authorities and practitioners over several months. This work then culminated in a one-day multi-stakeholder workshop which brought both ILK holders and coastal authorities and practitioners together to collaboratively identify pathways to integrate this knowledge into coastal and ocean management. In the Results and Discussion section the authors present and discuss five co-identified pathways to integrate ILK in coastal and ocean management which include: adopting contextual approaches to coastal and ocean management; increasing transparency and two-way communication between coastal authorities and users; increasing access to relevant and useable information; reviewing and amending relevant MSP legislation towards a stronger connection between MSP and Indigenous knowledge legislation; as well as amending legislation pertaining to access to coastal and marine areas. In the Conclusion it is argued that ILK coastal communities want to be meaningfully included in how their coastline and ocean resources are managed and also seek increased access to coastal areas. By highlighting pathways to include ILK and the knowledge holders themselves, this paper seeks to contribute to improved protection and sustainable management of marine resource use.